Co-digestion of petrochemical wastewater with activated manure in continuous stirred tank reactor for methane production - Siddique, Md. Nurul Islam (2015)
The combined challenges of environmental crisis and declining fossil fuel supplies are driving intensive research focused on alternative energy production. Particularly, today’s generation is facing two coexisting problems: the proper management of wastes generated from the industrial sectors, and the scarcity for novel resources of gasoline to meet up energy demand of civilization. Anaerobic co-digestion, a sustainable green technology, presents an outstanding opportunity for both energy conversion and pollution control. Therefore, it has become a core method treating organic wastes on account of its economic benefits of energy generation. The continuous stirred tank reactor (CSTR) can be defined as a sealed-tank digester equipped with mixing facility. Chemical pretreatment coupled with anaerobic co-digestion technology was applied on petrochemical wastewater using CSTR focusing on enhanced hydrolysis and methanogenesis. Batch experiments were performed, with applied H2O2 doses of 0.5%, 1% and 1.5% for contact times of 5, 10 and 15 min. Results revealed that 1% H2O2 dose (1.0mM Fe3+) for 5 min exposure elevated biodegradability index (BOD/COD) up to 35%. Subsequently, batch experiments were employed with various mixing proportions of petrochemical wastewater (PWW): dairy cattle manure (DCM): beef cattle manure (BCM), such as 25: 37: 38, 40: 30: 30, 50: 25: 25, 60: 20: 20, and 75: 12: 13. Results revealed that PWW: DCM: BCM ratio (50: 25: 25) provided maximum methane production. Although methane production is considered to get introverted by VFA accumulation leading to reactor instability during anaerobic digestion, a 10 mg/L of NH4HCO3 dosing and the co-digestion of PWW together with BCM and DCM caused 50% enhancement in methane production, followed by a 98±0.5% reduction in COD at 10 days hydraulic retention time. No VFA buildup was identified. In comparison with the digestion of PWW alone, methane yield increased by 50–60% under mesophilic conditions and 50–65% under thermophilic conditions due to co-digestion. This was induced by an optimum C: N ratio (30:1) of the feed stock ensuring microbial growth and buffering capacity. The anaerobic digestion, biogas generation, and energy assessment were analyzed for ten flow rates; 170, 220, 300, 370, 410, 475, 540, 600, 640 and 680 mL/day. The analytical data revealed that the environmentally complied optimum flow rate was 170 mL/day, for maximum methane generation. As the F/M proportion varied from 0.25 to 2.0 and organic loadings from 6.31-27.14 (g VS/L), however, it has been observed that the methane yield increased from 451.9±15 to 461.5±17 and 519.8±15 to 520.9±16 mL/ g VS as the F/M ratio increased from 0.25 to 0.5 for mesophilic and thermophilic states respectively but decreased gradually even when the F/M ratio increased up to 2. However, considering all the factors F/M ratio of 0.5 was observed to be the optimum to avoid system imbalance. This work may help in minimizing the environmental issues of petrochemical wastewater treatment in the future